Profilin1 is expressed in osteocytes and regulates cell shape and migration. Issue 1 (3rd May 2017) - Lin, Wanting; Izu, Yayoi; Smriti, Arayal; Kawasaki, Makiri; Pawaputanon, Chantida; Böttcher, Ralph T.; Costell, Mercedes; Moriyama, Keiji; Noda, Masaki; Ezura, Yoichi
Abstract : Osteocytes are the most abundant cells in bone and regulate bone metabolism in coordination with osteoblasts and osteoclasts. However, the molecules that control osteocytes are still incompletely understood. Profilin1 is an actin‐binding protein that is involved in actin polymerization. Osteocytes possess characteristic dendritic process formed based on actin cytoskeleton. Here, we examined the expression of profilin1 and its function in osteocytes. Profilin1 mRNA was expressed in osteocytic MLO‐Y4 cells and its levels were gradually increased along with the time in culture. With regard to functional aspect, knockdown of profilin1 by siRNA enhanced BMP‐induced increase in alkaline phosphatase expression levels in MLO‐Y4 cells. Profilin1 knockdown suppressed the levels of dendritic processes and migration of MLO‐Y4 cells. Since aging causes an increase in ROS in the body, we further examined the effects of hydrogen peroxide on the expression of profilin1. Hydrogen peroxide treatment increased the levels of profilin1 mRNA in MLO‐Y4 cells in contrast to the decline in alkaline phosphatase. Profilin1 was expressed not only in MLO‐Y4cells but also in the primary cultures of osteocytes. Importantly, profilin1 mRNA levels in primary cultures of osteocytes were higher than those in primary cultures of osteoblasts. To examine in vivo role of profilin1 in osteocytes, profilin1 was conditionally knocked out by using DMP1‐cre and profilin1 floxed mice. This conditional deletion of profilin1 specifically in osteocytes resulted in reduction in the levels of bone volume and bone mineral density. These data indicate that profilin1 is expressed in osteocytes and regulates cell shape, migration and bone mass. Abstract : Profilin1 knockdown reduces dendritic process formation in osteocytic MLO‐Y4 cells.